Research and assessment of potential groundwater exploitation reserves in coastal areas of Ninh Thuan province - Tran , Thi Thuy Huong; Trinh, Hoai Thu; Nguyen, Van Hoang (Vietnam Journal of Marine Science and Technology, 2023)
This paper presents the results and assessment of the groundwater exploitation reserves in coastal areas of Ninh Thuan province. The research was based on determining the exploitation reserves of all grid cells with dimensions 500 m × 500 m distributed in fresh-salted water areas of the Holocene (qh) and Pleistocene (qp) aquifers. Each grid was assigned the corrected hydrogeological parameter values (depth, gravity coefficient, hydraulic conductivity, and drawdown level). The calculation results show that the total amount of potential exploitation reserves in the entire qh and qp aquifers-distributed areas is 561.8 × 106 m3 per day, whereas in the freshwater area is 345.4 × 106 m3 per day (61.5%), and the saline water area is 216.4 × 106 m3 per day (38.5%). These potential exploitation reserves can be used for groundwater exploitation management and planning in Ninh Thuan province.